Prawa autorskie a młodziez akademicka. Konteksty prawne i społeczno-pedagogiczne - Sokołowska, Anna (Kultura-Społeczeństwo-Edukacja, 2013)
This article is an analysis of a role of copyrights in shaping forming of young creator’s attitude toward life. For that purpose, an attempt has been made to de ne the character and frames of legal and proprietorial protection of the creative process of university students. As copyrights protect author’s identity, practices violating such rights may lead to problems with nding and expressing one’s own identity, in particular against a role played by creativity in a proper development of human personality. A discussion on social and legal situation of youth as a subject to copyrights extends to juridical, psychological and pedagogical categories, while also undertaking, within a certain scope, an attempt to synthesise them. A basic conclusion provided in this article indicates a possibility of improving the quality of copyrights protection also through skilful guidance of young people’s consciousness.